PENGARUH GEMPA DAN GELOMBANG TSUNAMI DI PALU-DONGGALA TERHADAP ABNORMAL RETURN DAN VOLUME PERDAGANGAN PERUSAHAAN LQ45 YANG TERDAFTAR DI BEI - Khusnul Munawaroh; Noor Shodiq Askandar; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACT The purpose of this study is to analyze the effects of earthquake and tsunami waves in Palu-Donggala, which is indicated by the presence or absence of abnormal returns and trading volume activity. The population used in this study is LQ45 stock on the IDX. The sampling technique is a purposive sampling method. This research uses event studies for the observation period to show responses before and after the incident. The entire period of study was H-5 (before the event) and H + 5 (after the event). This study used secondary data, such as the daily stock price of the adjusted closing price of closing adjusted stock price of the IHSG. Data was calculated and analyzed using the paired T-test analysis method. The results showed that when looking at average abnormal return (AAR) and average trading volume (ATVA) activity, there was no difference between before and after the event.  Keywords: Average Abnormal Return, Average Trading Volume Activity, Event Study, earthquake and tsunami waves in Palu-Donggala.